Evaluating Effects of Natural Plant Extract on Ruminal Fermentation Using in vitro Gas Production Technique - Salamatazar, Mohammad; Doust-Nobar, Ramin Salamat; Sis, Naser Maheri; Shahryar, Habib Aghdam; Asadi, Yahya (Pakistan Journal of Nutrition, 2012)
The aim of this study was to determine effects of the increasing concentrations of thyme methanolic extract (0 and 0.3 ml/30 ml buffered rumen fluid) on Soybean Meal (SBM) degradability were studied by in vitro gas producing techniques. Fermentation of treatment samples were carried out with rumen fluids obtained from three mature cannulated steers in times of 2, 4, 6, 8, 12, 24, 48, 72 and 96 h were performed. The results showed that gas volume at 72 h incubation time (for 200 mg dry samples), of soybean meal and thyme methanolic extract (0.3 ml/30 ml buffered rumen fluid) were 62.91 and 37.64 (ml/200 mg DM) respectively. The gas production from soluble fraction (a), the gas production from insoluble fraction (b), rate constant of gas production during incubation (c) and the potential gas production (a+b) contents of soybean meal were 4.42 (ml/200 mg DM), 67.1 (ml/200 mg DM), 0.113 (ml/h) and 71.52 (ml/200 mg DM), while for thyme methanolic extract (0.3 ml/30 ml buffered rumen fluid) were 1.006 (ml/200 mg DM), 42.8 (ml/200 mg DM), 0.033 (ml/h) and 43.81 (ml/200 mg DM) respectively.